己知正项数列 $\left\{a_n\right\}$, 其前 $n$ 项和 $S_n$满足 $ a_n \left(2 S_n-a_n\right)=n, n \in N^*$.
(1) 求 $\left\{a_n\right\}$ 的通项公式;
(2) 证明: $\frac{1}{S_1^2}+\frac{1}{S_2^2}+\cdots+\frac{1}{S_n^2} < 2$.
【答案】 (1) 当 $n=1$ 时可得 $a_1=S_1=1$, 1 分
当 $n \geq 2$ 时, 由题意可得 $\left(S_n-S_{n-1}\right)\left(S_n+S_{n-1}\right)=n$, 即 $S_n^2-S_{n-1}^2=n$,
所以 $S_n^2=\left(S_n^2-S_{n-1}^2\right)+\cdots+\left(S_2^2-S_1^2\right)+S_1^2=n+(n-1)+\cdots+1=\frac{n(n+1)}{2}$, 即 $S_n=\sqrt{\frac{n(n+1)}{2}}$,
经检验,当 $n=1$ 时符合,所以 $S_n=\sqrt{\frac{n(n+1)}{2}} , n \in N^*$;
所以当 $n \geq 2$ 时, $a_n=S_n-S_{n-1}=\sqrt{\frac{n(n+1)}{2}}-\sqrt{\frac{n(n-1)}{2}}$,
经检验, 当 $n=1$ 时符合, 所以 $a_n=\sqrt{\frac{n(n+1)}{2}}-\sqrt{\frac{n(n-1)}{2}}, n \in N^* ; \ldots \ldots \ldots \ldots \ldots \ldots \ldots 6$ 分(不检验扣 1 分)

(2) 由 (1) 可得 $\frac{1}{S_n^2}=\frac{2}{n(n+1)}=2\left(\frac{1}{n}-\frac{1}{n+1}\right)$, 所以 $\frac{1}{S_1^2}+\frac{1}{S_2^2}+\cdots+\frac{1}{S_n^2}=2\left[\left(1-\frac{1}{2}\right)+\left(\frac{1}{2}-\frac{1}{3}\right)+\cdots+\left(\frac{1}{n}-\frac{1}{n+1}\right)\right]=2\left(1-\frac{1}{n+1}\right) < 2$, 命题得证. 12 分


系统推荐